PREVALENSI DAN POLA SENSITIVITAS Klebsiella pneumoniae DAN Escherichia coli PENGHASIL EXTENDED SPECTRUM BETALAKTAMASE DI RSPAD GATOT SOEBROTO TAHUN 2021 - Yusmaini, Hany; Bahar, Meiskha; Harfiani, Erna; Ufi Dewintera (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
ESBL-producing K. pneumoniae and E. coli are the Enterobacteriaceae that most commonly cause bacteriemia and nosocomial infections in the world. It is important to be aware of these bacteria to prevent an increase in infections with these resistant bacteria in hospitals. This research is a retrospective descriptive study, aiming to determine the prevalence of ESBL produced by K. Pneumoniae and E. coli and their sensitivity patterns. The data comes from clinical specimens that were examined for bacterial culture and antibiotic sensitivity tests in the Clinical Pathology Microbiology Lab in 2021. ESBL test using VITEK 2 compact tool. The results of the research were that E. coli was the most ESBL producing bacteria (50.9%) while K. pneumoniae was 20.9%. The highest prevalence of positive ESBL came from the ICU (41.4%) and the surgical ward (40.8%). Almost all rooms from which specimens were sent had a higher prevalence of positive ESBL E.coli, while for K.pneumoniae negative ESBL was higher. The most common types of positive specimens were bronchial lavage (67.4%) and wound swab (47.1%). Antibiotics that have high sensitivity to ESBL positive bacteria are Amikacin, Tigecycline and Meropenem.This research shows an increase in the prevalence of ESBL-producing K. pneumoniae and E. coli at the Gatot Soebroto Army Hospital, although it is still lower than several other national referral hospitals. Infection control, rational use of antimicrobials and prevention of transmission must continue to be pursued to reduce its prevalence.